Biocompatible Nanomaterials in Food Science, Technology, and Nutrient Drug Delivery: Recent Developments and Applications - Ranjha, Muhammad Modassar Ali Nawaz; Shafique, Bakhtawar; Rehman, Abdur; Mehmood, Arshad; Ali, Ahmad; Zahra, Syeda Mahvish; Roobab, Ume; Singh, Ajay; Ibrahim, Salam A.; Siddiqui, Shahida Anusha (Frontiers in Nutrition, 2022)
Nanomaterials exist as potential biocompatible materials in nature and are being synthesized to provide extraordinary characteristics in various food industry sectors. Synthesis of biocompatible nanomaterials requires modification in the shape, density, and size of nanomaterials. Biocompatible nanomaterials are synthesized to reduce toxicity, decrease adverse effects in the gastrointestinal tract, and enhance immune response. Nanomaterials can target organs and tissues. Nanomaterials are found to be effectively compatible by interacting with functional foods and nutraceuticals. Applications of these nanomaterials are novel strategies in food industries such as food safety, food processing, food quality, food packaging, and food labeling. Various functions like detection of toxins and pathogens; production of biocompatible packaging; enhancement in color, flavor, and aroma; processing edible film, and sensing authenticity of food product are being accomplished with no toxicity. This review provides a systematic study on the biocompatibility of nanomaterials. It highlights the synthesis of biocompatible nanomaterials and advanced functions of these nanomaterials in the production area, processing industry, safety improvement, quality control, edible packaging films, biocompatibility, current developments, legislations and regulations for Nano-products, health and safety concerns, toxicity and public perceptions for use of nanomaterials.